Faktor-Faktor Yang Mempengaruhi Penyerapan Anggaran Belanja Pemerintah Daerah: Proses Pengadaan Barang/Jasa Di Kabupaten Bolaang Mongondow Selatan - Rerung, Elypaz Donald; Karamoy, Herman; Pontoh, Winston (Universitas Sam Ratulangi, 2017)
Abstract. Government spending provides a wide range of services to the community. The most significant component of government spending relates to social security and welfare. It is the capital expenditure in Local Government Budget which is intended to finance development to promote such general welfare of the people. Budget absorption is one of the factors in evaluating Government performance to stimulate economic growth. Local Government revenue and expenditure budgets have significant influences to contribute the growth of regional economy if they are absorbed maximally. Budget absorption for goods and services procurement is generally slow. Additionally, budget realization often accumulates at the end of the year due to various problems in both administrative and technical aspects. This study aims to examine the effect of management commitment, bureaucratic environment, human resource competence and implementation of e-procurement towards budget absorption for goods and services procurement. This is a quantitative research and employed multiple regression analysis. The sample of the research is 63 Government employees whose responsibilities are in the budget and goods and services procurement. They are staff in commitment making, budget executing, authorizing or signing the cash disbursement, procurement working group and expenditure treasurer at 14 SKPD Bolaang Southern Mongondow. The result shows that management commitment, bureaucratic environment, and e-procurement implementation have positive and significant impacts to the budget absorption for goods and services procurements. Human resource competencies do not affect the budget absorption for goods and services procurement. The practical implication of this research suggests policy makers to improve human resources competencies for sufficient budget absorption.Keyword: Budget Absorption, Management Commitment, Bureaucracy Environment, Human Resource Competencies, e-Procurement Abstrak. Belanja modal dalam struktur APBD merupakan pengeluaran pemerintah yang mencerminkan dukungan pemerintah dalam pembangunan untuk kesejahteraan masyarakat. Pelaksanaan belanja modal tersebut dalam rangka peningkatan pelayanan publik oleh pemerintah dalam bentuk kebutuhan dasar. Penyerapan anggaran merupakan salah satu tolok ukur kinerja pemerintah dalam menggerakkan roda perekonomian. Anggaran pendapatan dan belanja daerah memiliki pengaruh yang cukup signifikan dalam mendorong pertumbuhan ekonomi daerah apabila terserap secara maksimal. Penyerapan anggaran terkait pengadaan barang/jasa pada umumnya lambat bahkan realisasinya seringkali menumpuk diakhir tahun karena berbagai permasalahan yang dihadapi baik dari aspek administrasi maupun dari aspek teknis. Penelitian ini bertujuan untuk menguji pengaruh komitmen manajemen, lingkungan birokrasi, kompetensi sumber daya manusia, dan penerapan e-procurement terhadap penyerapan anggaran terkait pengadaan barang/jasa. Metode penelitian ini adalah kuantitatif dengan regresi berganda. Sampel penelitian adalah 63 orang yang menduduki jabatan di bidang yang berkaitan dengan anggaran dan pengelola pengadaan barang/jasa, diantaranya adalah pejabat pembuat komitmen, pejabat pelaksana teknis kegiatan, pejabat penandatangan surat perintah membayar, kelompok kerja pengadaan dan bendahara pengeluaran pada 14 SKPD Pemerintah Kabupaten Bolaang Mongondow Selatan. Hasil penelitian menunjukkan bahwa komitmen manajemen, lingkungan birokrasi, dan penerapan e-procurement berpengaruh positif dan signifikan terhadap penyerapan anggaran terkait pengadaan barang/jasa. Kompetensi sumber daya manusia tidak berpengaruh terhadap penyerapan anggaran terkait pengadaan barang/jasa. Implikasi praktis dari penelitian ini adalah untuk memberi masukan kepada pengambil kebijakan pada pemerintah daerah untuk lebih mengoptimalkan kompetensi sumber daya manusia dalam rangka peningkatan penyerapan anggaran.Kata kunci: Penyerapan Anggaran, Komitmen Manajemen, Lingkungan Birokrasi, Kompetensi Sumber Daya Manusia, e-Procurement.